In vivo Editing of the Human Mutant Rhodopsin Gene by Electroporation of Plasmid-based CRISPR/Cas9 in the Mouse Retina - Maria Carmela Latella; Maria Teresa Di Salvo; Fabienne Cocchiarella; Daniela Benati; Giulia Grisendi; Antonella Comitato; Valeria Marigo; Alessandra Recchia (Elsevier, 2016)
The bacterial CRISPR/Cas system has proven to be an efficient tool for genetic manipulation in various organisms. Here we show the application of CRISPR-Cas9 technology to edit the human Rhodopsin (RHO) gene in a mouse model for autosomal dominant Retinitis Pigmentosa. We designed single or double sgRNAs to knock-down mutant RHO expression by targeting exon 1 of the RHO gene carrying the P23H dominant mutation. By delivering Cas9 and sgRNAs in a single plasmid we induced an efficient gene editing in vitro, in HeLa cells engineered to constitutively express the P23H mutant RHO allele. Similarly, after subretinal electroporation of the CRISPR/Cas9 plasmid expressing two sgRNAs into P23H RHO transgenic mice, we scored specific gene editing as well as significant reduction of the mutant RHO protein. Successful in vivo application of the CRISPR/Cas9 system confirms its efficacy as a genetic engineering tool in photoreceptor cells.